2021
DOI: 10.2991/absr.k.210609.026
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Quality of Duck’s and Chicken’s Meat Using African Leaf (Vernonia amygdalina)

Abstract: Animal product with high body weight and low cholesterol will improve the quality of the product. This study aims to determine the response of male local duck and broiler chickens, which are given African leaf meal (ALM) in their rations, to body weight and blood lipid content. The treatment that will be given is the level of ALM usage as many as 5 levels (0%; 0.5%; 1.0%; 1.5% and 2.0%). The treatments were analyzed by completely randomized design (CRD) with 4 replications. The treatment given to 100 broilers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…At 10 mL/L VALE (T1), cholesterol levels were decreased and were reduced at 20 mL/L (T2), but T2 and T3 groups were not significantly different. Vernonia amygdalina leaf extract contains antioxidants that reduce bile acid secretion and cholesterol deposition in meat, in agreement with Suhaemi and Hidayati [21], who showed that V. amygdalina leaf powder (1-2%) reduced cholesterol levels in broiler meat. Vernonia amygdalina contains many antioxidants [41,42] which inhibit HMG CoA reductase and lipase enzymes [43].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At 10 mL/L VALE (T1), cholesterol levels were decreased and were reduced at 20 mL/L (T2), but T2 and T3 groups were not significantly different. Vernonia amygdalina leaf extract contains antioxidants that reduce bile acid secretion and cholesterol deposition in meat, in agreement with Suhaemi and Hidayati [21], who showed that V. amygdalina leaf powder (1-2%) reduced cholesterol levels in broiler meat. Vernonia amygdalina contains many antioxidants [41,42] which inhibit HMG CoA reductase and lipase enzymes [43].…”
Section: Discussionsupporting
confidence: 87%
“…Supplemented V. amygdalina (30 mL/L) juice in drinking water increased carcass weight but percentages were not significantly different [ 20 ]. Suhaemi and Hidayati [ 21 ] showed that African leaves reduced cholesterol levels in broiler meat. Efforts to overcome stress in quail using VALE also improved egg production and quality [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 100 g serving, while chicken, turkey and duck provides 27.3 g, 28.5 g and 20.3 g of protein, respectively, and 13.6 g, 7.39 g and 22.85 g of fats, respectively (Mazmanyan, 2021). However, the high level of cholesterol in duck meat and broiler chickens often limits their consumption (Suhaemi, Hidayat, 2020). In contrast, quail meat has less fat and cholesterol due low fat accumulation between its thin skin tissues (Farag et al, 2021).…”
Section: Introductionmentioning
confidence: 99%